Age of the Marwar Supergroup, NW India: A note on the U–Pb geochronology of Jodhpur Group felsic volcanics - Huiru Xu (Geoscience Frontiers, 2022)
The Marwar Supergroup (NW Peninsular India) is thought to be of Ediacaran-Cambrian age, based on previous paleontological and geochronological studies. However, direct constraints on the onset of sedimentation within the Marwar basin are still scarce. In this study, we report U–Pb zircon, LA-ICP-MS, and SIMS ages from the Chhoti Khatu felsic volcanic rocks, interlayered with the Jodhpur Group sandstones (Lower Marwar Supergroup). The cathodoluminescence images of the zircons indicate complex morphologies, and core-rim textures coupled with the wide range of ages indicate that they are likely inherited or in the case of thin poorly indurated ash-beds, detrital in origin. The age spectra of 68 zircon analyses from our sampling display a dominant 800–900 Ma age peak corresponding to the age of basement “Erinpura granite” rocks in the region. The youngest inherited zircon from a felsic ash layer yielded a U–Pb age of 651 Ma ± 18 Ma that, together with previous studies and paleontological evidence, indicates a post-Cryogenian age for the initiation of Marwar sedimentation following a ~125 Ma hiatus between the end of Malani magmatism and Marwar deposition.